Before the freeze: otoliths from the Eocene of Seymour Island, Antarctica, reveal dominance of gadiform fishes (Teleostei) - Schwarzhans, Werner; Mörs, Thomas; Engelbrecht, Andrea; Reguero, Marcelo Alfredo; Kriwet, Jürgen (Journal of Systematic Palaeontology)
The first record of fossil teleostean otoliths from Antarctica is reported. The fossils were obtained from late Early Eocene shell beds of the La Meseta Formation, Seymour Island that represent the last temperate marine climate phase in Antarctica prior to the onset of cooling and subsequent glaciation during the late Eocene. A total of 17 otolith-based teleost taxa are recognized, with 10 being identifiable to species level containing nine new species and one new genus: Argentina antarctica sp. nov., Diaphus? marambionis sp. nov., Macruronus eastmani sp. nov., Coelorinchus balushkini sp. nov., Coelorinchus nordenskjoeldi sp. nov., Palimphemus seymourensis sp. nov., Hoplobrotula? antipoda sp. nov., Notoberyx cionei gen. et sp. nov. and Cepola anderssoni sp. nov. Macruronus eastmani sp. nov. is also known from the late Eocene of Southern Australia, and Tripterophycis immutatus Schwarzhans, widespread in the southern oceans during the Eocene, has been recorded from New Zealand, southern Australia, and now Antarctica. The otolith assemblage shows a typical composition of temperate fishes dominated by gadiforms, very similar at genus and family levels to associations known from middle Eocene strata of New Zealand and the late Eocene of southern Australia, but also to the temperate Northern Hemisphere associations from the Paleocene of Denmark. The Seymour Island fauna bridges a gap in the record of global temperate marine teleost faunas during the early Eocene climate maximum. The dominant gadiforms are interpreted as the main temperate faunal component, as in the Paleocene of Denmark. Here they are represented by the families Moridae, Merlucciidae (Macruroninae), Macrouridae and Gadidae. Nowadays Gadidae are a chiefly Northern Hemisphere temperate family. Moridae, Macruroninae and Macrouridae live today on the lower shelf to deep-water or mesopelagically with Macruroninae being restricted to the Southern Ocean. The extant endemic Antarctic gadiform family Muraenolepididae is missing, as are the dominant modern ...